2017
DOI: 10.1371/journal.pone.0181835
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the tea oil camellia (Camellia oleifera) reveals candidate drought stress genes

Abstract: BackgroundThe tea-oil camellia (Camellia oleifera) is the most important oil plant in southern China, and has a strong resistance to drought and barren soil. Understanding the molecular mechanisms of drought tolerance would greatly promote its cultivation and molecular breeding.ResultsIn total, we obtained 76,585 unigenes with an average length of 810 bp and an N50 of 1,092 bp. We mapped all the unigenes to the NCBI ‘nr’ (non-redundant), SwissProt, KEGG, and clusters of orthologous groups (COG) databases, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 68 publications
8
44
0
Order By: Relevance
“…This tendency implies that the higher the degree of drought, the more obvious the effect on gene expression in plants. Similar results were also reported on other plants, such as Camellia oleifera (Dong et al 2017;Xia et al 2014) and Cicer arietinum L. (Mahdavi et al 2018). According to the GO analysis, most of the DEGs were involved in ''integral component of membrane'' ''oxidation-reduction process'', ''metal ion binding'' and ''DNA binding'' from the seven pairs mentioned earlier.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This tendency implies that the higher the degree of drought, the more obvious the effect on gene expression in plants. Similar results were also reported on other plants, such as Camellia oleifera (Dong et al 2017;Xia et al 2014) and Cicer arietinum L. (Mahdavi et al 2018). According to the GO analysis, most of the DEGs were involved in ''integral component of membrane'' ''oxidation-reduction process'', ''metal ion binding'' and ''DNA binding'' from the seven pairs mentioned earlier.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies (Agarwal et al 2016;Yoshida et al 2015;Liu et al 2016) have reported that TFs were considered to have vital roles in accommodating and resisting drought conditions. We identified abundant TFs belonging to the bHLH (413), MYB (288), MYB-like (269), C2H2 (255), and bZIP (217) families, which is consistent with reports on kabuli chickpea (Cicer arietinum L.) (Mahdavi et al 2018) and tea oil camellia (Camellia oleifera) (Dong et al 2017). Following this, we would like to select several key TFs as candidates for functional verification.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Normalizing results with one or more appropriate internal RGs is a simple and popular method for controlling error in qRT-PCR assays. To date, a few housekeeping genes have been rigorously identified and used as RGs in tea plants under abiotic stresses, such as cold, barrenness, drought, photoperiod and exogenous application of plant hormones (auxin, ABA, GA, IAA, MeJA and SA) 25,26,28,[32][33][34] , leaf developmental stages and even different organs 26,35 . These results demonstrate that identifying appropriate RGs for target gene expression analysis under different experimental conditions is an essential prerequisite for developing a qPCR assay of tea plants.…”
Section: Discussionmentioning
confidence: 99%
“…Its fruit contains high-quality oil, commonly known as tea oil or camellia oil, which has 82%-84% unsaturated fatty acids, 68%-77% monounsaturated fatty acids, 67.7%-76.7% oleic acid, and 7%-14% polyunsaturated acid. The composition is similar to that of olive oil [2], hence it is called eastern olive oil [3]. Tea oil has also been widely used for cosmetic and medicinal purposes [4].…”
Section: Introductionmentioning
confidence: 99%